CRISPR/Cas9-Targeted Mutagenesis of BnaFAE1 Genes Confers Low-Erucic Acid in Brassica napus - Liu, Yunhao; Du, Zhuolin; Lin, Shengli; Li, Haoming; Lu, Shaoping; Guo, Liang; Tang, Shan (Frontiers in Plant Science, 2022)
Rapeseed (Brassica napus) is an important oilseed crop widely planted in the world, providing substantial edible oil and other nutrients for mankind. The composition of fatty acids affects the edible and processing quality of vegetable oils, among which erucic acid (EA) is potentially to cause health problems. Therefore, low erucic acid (LEA) has always been a breeding trait of B. napus. Fatty acid elongase 1 (FAE1) plays a decisive role in the synthesis of EA. There are two functional homologous copies of FAE1 on the A08 and C03 chromosomes in B. napus. In this study, we used CRISPR/Cas9 technology to create targeted mutations on these two homologous copies of BnaFAE1 in three B. napus germplasms with high EA (>30%) and high oil (>50%). Our results show that the EA content was significantly reduced by more than 10 percentage points in the mutant of BnaC03.FAE1 (c03), while the double mutation of BnaA08.FAE1 and BnaC03.FAE1 (a08c03) resulted in nearly zero EA in three BnaFAE1-edited germplasms, and the oleic acid content was increased in different degrees. In addition, knockout of BnaA08.FAE1 or/and BnaC03.FAE1 mildly decreased seed oil content, but had no significant effect on other agronomic traits. In general, we successfully created low EA germplasms of B. napus, which provides a feasible way for future low EA breeding.